Enhancing the Removal of Sorbed Crude Oil from Soil Through Multiple Oxidation Steps in Stepwise Fenton Processes. Issue 5 (4th July 2018) - Xu, Jinlan; Yang, Chengwei; Li, Lu; Huang, Tinglin; Huang, Rulei
ABSTRACT: The stepwise Fenton oxidation process, in which hydrogen peroxide (H2 O2 ) is added in a step-by-step manner instead of at the beginning, can achieve better sorbed crude oil removal effects. The results showed that if a high ratio of sorbed total petroleum hydrocarbon (TPH) was present in soil samples S1 (100%, initial TPH: 10, 009 mg/kg) and S2 (94.2%, initial TPH: 4850 mg/kg), the TPH was oxidized in each step. In addition, the total TPH removal efficiency was 49.6% compared with the 27.9% achieved in conventional Fenton oxidation in which all H2 O2 was added at the beginning. Nevertheless, when the ratio of sorbed TPH in the soil sample S3 was low (45.3%, initial TPH: 2850 mg/kg), the TPH removal efficiency was 18.9%, which was slightly higher than 18.2% achieved in the conventional Fenton process because if the sorbed TPH concentration was low, the sorbed TPH was mainly removed in the first step. The second and the third step resulted in long-chain alkanes entering the aqueous phase rather than removing them from the soil, which posed environmental risk. Therefore, it is clear that stepwise Fenton oxidation could improve sorbed TPH removal efficiency when the sorbed TPH concentration in the soil is high.